The noradrenergic projection from the locus coeruleus to the cochlear root neurons in rats - Hormigo, Sebastián; Gómez-Nieto, Ricardo; Castellano, Orlando; Herrero-Turrion, Manuel Javier; Lopez, Dolores Estilita; Horta-Júnior, José de Anchieta de Castro e [UNESP] (Springer, 2015)
The cochlear root neurons (CRNs) are key components of the primary acoustic startle circuit; mediating auditory alert and escape behaviors in rats. They receive a great variety of inputs which serve to elicit and modulate the acoustic startle reflex (ASR). Recently, our group has suggested that CRNs receive inputs from the locus coeruleus (LC), a noradrenergic nucleus which participates in attention and alertness. Here, we map the efferent projection patterns of LC neurons and confirm the existence of the LC-CRN projection using both anterograde and retrograde tract tracers. Our results show that each LC projects to the CRNs of both sides with a clear ipsilateral predominance. The LC axons terminate as small endings distributed preferentially on the cell body and primary dendrites of CRNs. Using light and confocal microscopy, we show a strong immunoreactivity for tyrosine hydroxylase and dopamine beta-hydroxylase in these terminals, indicating noradrenaline release. We further studied the noradrenergic system using gene expression analysis (RT-qPCR) and immunohistochemistry to detect specific noradrenergic receptor subunits in the cochlear nerve root. Our results indicate that CRNs contain a noradrenergic receptor profile sufficient to modulate the ASR, and also show important gender-specific differences in their gene expression. 3D reconstruction analysis confirms the presence of sexual dimorphism in the density and distribution of LC neurons. Our study describes a coerulean noradrenergic projection to the CRNs that might contribute to neural processes underlying sensory gating of the ASR, and also provides an explanation for the gender differences observed in the behavioral paradigm.
Keywords: Acoustic startle reflex; Gender differences; Neuronal tracers; Noradrenergic receptors; Sensory gating; 3D reconstruction